Effect of tropical fruit juices on dentine permeability and erosive ability in removing the smear layer: An in vitro study - Kanittha Kijsamanmith; Rudee Surarit; Noppakun Vongsavan (Elsevier, 2016)
Background/purpose: Acidic diet is one major cause of dentine hypersensitivity. The objective of this study was to determine the effects of different tropical fruit juices on dentine permeability and their erosive ability to remove the smear layer in extracted human teeth. Materials and methods: Thirty-six noncarious human premolars were used, and the dentine was exposed at the tip of the buccal cusp by cutting a cavity (diameter 3 mm, depth 3 mm). Permeability of the dentine was tested under different conditions: with a smear layer and 5 minutes after the application of freshly squeezed green mango, lime, tamarind, and starfruit juices. The smear layer was created before each treatment by gently cutting the dentine with a diamond bur. In the final treatment, the dentine was etched with 37% phosphoric acid for 30 seconds. The erosive ability of these fruit juices to remove the smear layer was also examined using a scanning electron microscope. Results: Results revealed that application of green mango, tamarind, lime, and starfruit juices for 5 minutes significantly increased dentine permeability by 128.2%, 73.4%, 80.6%, and 70.4%, respectively (P < 0.05, Friedman repeated measures analysis of variance on ranks). The corresponding value of 37% phosphoric acid was 125.1%. Scanning electron microscopy data showed that green mango and lime juices had very strong erosive ability to remove the smear layer, similar to 37% phosphoric acid. Conclusion: We conclude that tropical fruit juices, especially green mango and lime, increase dentine permeability and have a strong erosive ability to remove the smear layer, which causes dentine hypersensitivity.